2016
DOI: 10.1080/ac.71.2.3141852
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and psychopathology in patients with acute myocardial infarction

Abstract: In this clinical setting the deficit of emotion expression points to the need of psychotherapeutic intervention in patients after an AMI event occurs, to improve prognosis and well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 0 publications
0
14
2
Order By: Relevance
“…Alexithymia has been associated with an expanding range of somatic pathologies such as inflammatory bowel disease, myocardial infarction, chronic respiratory diseases, dermatologic conditions, chronic pain, neuromuscular disorders, diabetes and food allergy (). It has been found to increase unhealthy behaviours and susceptibility to organic diseases notably immune‐mediated disorders via physiological, behavioural, cognitive or social pathways from childhood leading to adverse outcomes in adulthood .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alexithymia has been associated with an expanding range of somatic pathologies such as inflammatory bowel disease, myocardial infarction, chronic respiratory diseases, dermatologic conditions, chronic pain, neuromuscular disorders, diabetes and food allergy (). It has been found to increase unhealthy behaviours and susceptibility to organic diseases notably immune‐mediated disorders via physiological, behavioural, cognitive or social pathways from childhood leading to adverse outcomes in adulthood .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on different chronic diseases highlighted the need to develop and test alexithymia interventions and examine their effects on important disease‐related variables (e.g. HRQL, symptoms) . A controlled study found a significant decrease in TAS scores among cardiac patients in psychological treatment but not in controls.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial infarction (MI) is still one of the most important health problems today despite improvements in diagnosis and treatment. In recent years, the interaction between emotional diseases and heart diseases has been noted, and the connection of mental disorders with cardiac diseases has been pointed out (1).…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have reported a close relationship between cardiac diseases and alexithymia (1,(7)(8)(9). Oxygen deprivation in MI requires urgent medical attention and causes damage to heart tissue and death of tissue, which requires urgency for early diagnosis and reperfusion treatment for good prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Alexithymia has been found in patients suffering chronic pain with no identifiable cause, including patients with fibromyalgia (van Middendorp et al, 2008), depression and psychosomatic illnesses (Kusevic et al, 2013), high blood pressure, Crohn's disease, psychiatric patients (panic and anxiety disorders, depression), and those with kidney and rheumatic diseases (Marchesi et al, 2013;Sayar, Kirmayer, & Taillefer, 2004;Silva, Freitas, Moreira, Santos, & Almeida, 2016;Di Tella & Castelli, 2016). However, the prevalence of alexithymia has also been found to be as high as 7% among the general population (Steinweg, Dallas, & Rea, 2011) without any link to specific disorders (Cox, Kuch, Parker, Shulman, & Evans, 1994;Praceres et al, 2000;Yoshida, 2000Yoshida, , 2007.…”
mentioning
confidence: 99%